Features of fracture surface in a fully lamellar TiAl-base alloy. (March 2015) - Ding, Rengen; Li, Hangyue; Hu, Dawei; Martin, Nigel; Dixon, Mark; Bowen, Paul
Abstract: The deformation mechanisms associated with different fracture surface appearances of a fatigue tested lamellar TiAl-based alloy have been studied in detail by focussed ion beam and transmission electron microscopy. The results show that linear markings within translamellar plates correspond to twins and/or slip bands. The markings in interlamellar region are associated with the crack propagation from a lamellar boundary to another. The fan-like region with linear markings belongs to a γ grain and the markings are related to twins. Intralamellar crack propagation is associated with twin–twin interaction within a γ lamella. Highlights: Marking in translamellar area is intersection between twin in γ plate and fracture surface. Marking in interlamellar area is formed via crack deviation from an interface to another. Marking in intralamellar surface is related to cracking induced by twin–twin interaction. Marking in fan-like area is intersection between twin within γ grain and fracture surface.